Levelling the Playing Field: The Role of Workshops to Explore How People With Parkinson's Use Music for Mood and Movement Management as Part of a Patient and Public Involvement Strategy - Rose, Dawn C.; Poliakoff, Ellen; Hadley, Rebecca; Guérin, Ségolène M. R.; Phillips, Michelle; Young, William R. (Frontiers in Rehabilitation Sciences, 2022)
From a humanistic perspective, participatory processes in research find support on both ethical and moral grounds. In practical terms however, it is often difficult to establish protocols that best honour (i.e., elicit, capture, and integrate) the opinions of individuals and groups that represent the various specific stakeholders (e.g., from allied health, scientific, and academic disciplines) needed to investigate complex phenomena. Here, we describe a consultation process (funded by Parkinson's UK) devised to explore use of music among people with Parkinson's in relation to potential applications to enhance quality of life. People with Parkinson's were paired with researchers in order to discuss music on an equal footing so as to enable participant empowerment. We describe outcomes that demonstrate avenues of success as a result of this approach and additional insights gained through these processes in the hope of informing future practice. It has been our experience that researchers must establish a balance between (a) ensuring methodological rigour within an appropriate framework, and (b) facilitating informal “playtime” that develops connectivity between participants and enables both creative thinking and reflexive practice amongst stakeholders. We encourage researchers not to underestimate “playtime” as an important vehicle to foster this social interactivity and fuel the good will required to conduct inclusive and relevant research.